2015
DOI: 10.1007/s11239-015-1190-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two anti-coagulation plans on the prevention of PVST after laparoscopic splenectomy and esophagogastric devascularization

Abstract: Cirrhosis and portal hypertension (PH) has a high incidence in China. Laparoscopic splenectomy and esophagogastric devascularization (LS + ED) was confirmed as an effective and safe surgical approach. But compared to open surgery (OS + ED), the rate of portal vein system thrombosis (PVST) was found to be higher after LS + ED. PVST is a common and potentially life-threatening complication after LS + ED in patients with cirrhosis and PH. Anti-coagulation therapy should be given early, but no standard plan for PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
12
1
Order By: Relevance
“…That is to say, postoperative platelet counts may not be a risk factor for postoperative PVT. Furthermore, the total PVT rate was 20.8% (15/72) without any anticoagulant therapy, which was lower than that previously reported [16, 17]. The postoperative esophagogastric varices rebleeding rate was low in the LSEGDS group (6.2%, 2/32) compared with the LEGDS group (10%, 4/40) but the difference was not significant.…”
Section: Discussioncontrasting
confidence: 60%
“…That is to say, postoperative platelet counts may not be a risk factor for postoperative PVT. Furthermore, the total PVT rate was 20.8% (15/72) without any anticoagulant therapy, which was lower than that previously reported [16, 17]. The postoperative esophagogastric varices rebleeding rate was low in the LSEGDS group (6.2%, 2/32) compared with the LEGDS group (10%, 4/40) but the difference was not significant.…”
Section: Discussioncontrasting
confidence: 60%
“…The incidence of PVST, which is measured in patients with wider internal diameter of the splenic vein, as well as portal vein and increased portal vein flow, remains high, indicating that these indicators can be used as markers of PVST prediction in cirrhotic patients with PH and EGVB. Early heparin therapy should be recommended in patients who have these factors after the operation [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through the literature search and selection based on the criteria above, we identified 2027 relevant citations, and finally 11 studies (from 2000 to 2016) containing 1153 patients [22–32] were included in this meta-analysis (Figure 1). These 11 Asian studies (Table 1) reported 8 anticoagulation strategies including: Antithrombin III (ATIII), low-molecular-weight heparin (LMWH) plus Warfarin plus Aspirin, LMWH plus Warfarin, Urokinase + Aspirin, Warfarin, Alprostadil, Aspirin, LMWH plus Aspirin.…”
Section: Resultsmentioning
confidence: 99%